Avelumab plus axitinib vs sunitinib for advanced renal cell carcinoma: Japanese subgroup analysis from JAVELIN Renal 101. Issue 3 (5th February 2020) - Uemura, Motohide; Tomita, Yoshihiko; Miyake, Hideaki; Hatakeyama, Shingo; Kanayama, Hiro‐omi; Numakura, Kazuyuki; Takagi, Toshio; Kato, Tomoyuki; Eto, Masatoshi; Obara, Wataru; Uemura, Hirotsugu; Choueiri, Toni K.; et al.
Abstract: The phase 3 JAVELIN Renal 101 trial of avelumab + axitinib vs sunitinib in patients with treatment‐naive advanced renal cell carcinoma (RCC) demonstrated significantly improved progression‐free survival (PFS) and higher objective response rate (ORR) with the combination vs sunitinib. Japanese patients enrolled in the study (N = 67) were randomized to receive avelumab + axitinib (N = 33) or sunitinib (N = 34); 67% vs 59% had PD‐L1+ tumors (≥1% of immune cells) and 6%/64%/27% vs 6%/82%/12% had International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) favorable/intermediate/poor risk status. In patients who received avelumab + axitinib vs sunitinib, median PFS (95% confidence interval [CI]) was not estimable (8.1 months, not estimable) vs 11.2 months (1.6 months, not estimable) (hazard ratio [HR], 0.49; 95% CI, 0.152, 1.563) in patients with PD‐L1+ tumors and 16.6 months (8.1 months, not estimable) vs 11.2 months (4.2 months, not estimable) (HR, 0.66; 95% CI, 0.296, 1.464) in patients irrespective of PD‐L1 expression. Median overall survival (OS) has not been reached in either arm in patients with PD‐L1+ tumors and irrespective of PD‐L1 expression. ORR (95% CI) was 60.6% (42.1%, 77.1%) vs 17.6% (6.8%, 34.5%) in patients irrespective of PD‐L1 expression. Common treatment‐emergent adverse events (all grade; grade ≥3) in each arm were hand‐foot syndrome (64%; 9% vs 71%; 9%), hypertension (55%; 30% vs 44%; 18%), hypothyroidism (55%; 0% vs 24%; 0%), dysgeusia (21%; 0% vs 56%; 0%) and platelet count decreased (3%; 0% vs 65%; 32%). Avelumab + axitinib was efficacious and tolerable in treatment‐naive Japanese patients with advanced RCC, which is consistent with results in the overall population. Abstract : The phase 3 JAVELIN Renal 101 trial of avelumab + axitinib vs sunitinib in patients with treatment‐naive advanced renal cell carcinoma (RCC) demonstrated significantly improved progression‐free survival (PFS) and higher objective response rate (ORR) with the combination vs sunitinib. In Japanese patients who received avelumab + axitinib vs sunitinib, median PFS (95% CI) was not estimable (8.1 months, not estimable) vs 11.2 months (1.6 months, not estimable) (HR, 0.49; 95% CI, 0.152, 1.563) in patients with PD‐L1+ tumors and 16.6 months (8.1 months, not estimable) vs 11.2 months (4.2 months, not estimable) (HR, 0.66; 95% CI, 0.296, 1.464) in patients irrespective of PD‐L1 expression. Avelumab + axitinib was efficacious and tolerable in treatment‐naive Japanese patients with advanced RCC, which is consistent with results in the overall population.